Reflections for the World of Education: The Influence of the Role of Teachers on Student Learning Motivation - Selviana Ronsumbre; Martha Betaubun; Adi Sumarsono; Kharisma Caisar M. S. Setlight; Kristian Paruty Lewier (Universitas Muhammadiyah Enrekang, 2023)
The main capital of teachers is to foster students' interest in learning and become true learners so that students can apply their knowledge in everyday life. Therefore, apart from being educators, teachers also have other roles in the teaching and learning process, namely as motivators, evaluators and facilitators. Through the role of teachers in learning, students are able to show their perseverance in learning in order to achieve learning completeness. Therefore, teaching and learning activities do not only lie with teachers but students also interfere in the teaching and learning process. Referring to the complexity of the learning system which includes the importance of the role of the teacher and student motivation during learning, the purpose of this study is to examine the correlation between the role of the teacher and student learning motivation. The study used a combined method (quantitative and qualitative), where the subjects in this study were grade X students of SMK Negeri 2 Tourism Merauke with a total of 25 students. Data in this study were collected through questionnaires and observations. As a result, there is a close relationship between the role of teachers and student motivation in learning. This is also evidenced by the results of data processing using SPSS.25 software. with criteria If the sig > 0.05 accept Ho, From data processing obtained sig 0.038 < 0.05 means that Ho is rejected. Thus there is a significant correlation or relationship between the role of teachers and with student learning motivation in learning in grade 10 of SMK Negeri 2 Tourism Merauke, South Papua. Therefore, the success of education programs begins with the role of teachers in managing education.